ISLAM DAN ADAT DALAM PERNIKAHAN MASYARAKAT BUGIS DI PAPUA BARAT - Ismail Suardi Wekke (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2012)
Human life continuity is started on of them from marriage. Thisinstitution is perceived as a legal form in order to extend the generation. Inaddition, it is a need to formulate the marriage in daily life. Bugis society is wellknownas a group that have skill to adapt and open-minded to receiveinnovation. Therefore, this research will explore the relation between Islam andtradition in the context of Bugis society in West Papua. Research data werecollected from participant observation and in-depth interview. During ninemonths this research conducted through the province, except Teluk Wondamaand Raja Ampat. During research, ethnographic principals were applied tounderstand data. Observation guidelines and question list to guide datacollection. Research findings indicate Bugis society is far and they don